The Use of Dynamic Oriented Briefemergency Psychotherapy in Traumatic Problems of Adolescents: Case Report - Çitil Akyol, Canan; Yıldırım, Taşkın (Current Studies in Social Sciences VI, 2023)
Divorce is a stressful process for the children as it requires them to readopt to the new family and school life and new friends. Although some teenagers receive psychological help from the experts following their parents’ divorce, some others become introverted due to their developmental period or can exhibit risky behaviors. This study aims to describe the application process of brief-intensive-emergency psychotherapy, which has proved its success on depression, mourning and traumatic events, with teenagers going through their parents’ divorce. In this study, six sessions of brief-intensive-emergency psychotherapy were carried out with a teenager with divorced parents. The client was given Symptom Check List (SCL-90-R), Hacettepe Personality Inventory, Beier Sentence Completion Test (Form B) as pretest-posttest and the effects of brief-intensive-emergency psychotherapy on this client were examined.